A road map for developing novel decision support system (DSS) for disseminating integrated pest management (IPM) technologies - Tonle, F.B.; Niassy, S.; Ndadji, M.M.Z.; Tchendji, M.T.; Nzeukou, A.; Mudereri, B.T.; Senagi, K.; Tonnang, H.E.Z. (Elsevier, 2024)
Integrated Pest Management (IPM) technologies offer effective solutions to reduce the negative effects of crop pests while considering human and environmental health. However, disseminating these technologies faces several barriers, with one of the most significant being the lack of farmer awareness regarding their availability, deployment, and uptake. Digital tools are perceived as a new form of leverage for overcoming these barriers. This study analyzes current IPM digital tools and their potential to boost farmers’ awareness of the deployment and adoption of IPM technologies. From a software engineering perspective, this study aims to emphasize the critical functionalities and limitations of various IPM dissemination tools. It provides valuable insights to improve the adoption process and streamline the dissemination of IPM technologies. Through a systematic search in Google, Scopus and Web of Science for journal articles, over 32 dissemination tools were identified. The study thoroughly assesses these tools and identifies 5 main limitations hindering their regular use, especially in developing countries. Among the most significant limitations are the inadequate representation of tools developed in developing countries, lack of agroecological customization, and insufficient offline functionalities. Building on these findings, a user-centered design is employed to propose a software architecture for a novel Decision Support System (DSS) tailored to farmers and experts. The architecture comprises a local database for offline access, a mapping engine for data visualization, a conversation module with a triangulation engine for knowledge sharing, and an agroecology engine for technology recommendation based on an agroecological classification of the user’s landscape. Drawing from the review, identified limitations, and the proposed architecture, we illustrate how the resulting novel DSS is anticipated to improve the dissemination of IPM technologies.